Sipp Application Development Effort in Supporting the Digitalization of Tri Dharma at The Universitas Negeri Semarang - Setiawan, Avi Budi; Widyastuti, Ariyani; Putra, Anggyi Trisnawan; uminar; Wicaksana, Tania (Future Science, 2021)
Technology has helped humans in various fields, for example in the field of research and service. The Institute for Research and Community Service (LPPM) Universitas Negeri Semarang (UNNES) in its role in realizing the responsibility for the Tri Dharma of Higher Education, has changed the procedure for evaluating the instrument which was originally manual to be more effective and efficient through an application called SIPP (Management Information System). Research and Service) which can be accessed on the website. This change is expected to create even better conditions. However, these existing facilities are not well received. This can be seen from the many researchers who are late in collecting research instruments and even less familiar with this SIPP application. Data analysis techniques used in this study include transcripts of the results of field surveys, observations and interviews, data reduction, analysis, data interpretation and triangulation.